Study on Reactive Blue Adsorption on Raw and Modified Wheat Straw Using Fixed-Bed Column - Taha, Alaa; Mousa, Khalid M. (Al-Nahrain Journal for Engineering Sciences, 2021)
The intention of this study was to explore the efficiency and feasibility of adsorption of Reactive Blue dye (H3R) used in textile industries using Raw wheat straw (RWS) and Modified wheat straw (MWS) as a low-cost adsorbent. Wheat straw was modified using cationic surfactant (CTAB) to study the improvement of dye removal. The properties of Raw and Modified wheat straw are studied by means of Fourier transform infrared (FTIR) and scanning electron microscope (SEM) analyses to determine the functional groups and the nature of their surface. Continuous experiments were done by fixed-bed column to study the characteristics of the breakthrough curve using different bed heights and flow rates. Results showed that the breakthrough time increases with increasing bed height and decreasing flow rate, in turn results into higher removal capacity. Results also showed a higher flow rate lead a lower adsorption capacity due to insufficient residence time. Bed depth service time model (BDST), Adam-Bohart and Thomas models were used to predict the breakthrough curves and to determine the adsorption capacity of the column. The highest bed capacity of 12.95 and 32.2 mg/g for MWS was obtained using 10 mg/L, 10 cm bed height at 10 mL/min and 30 mL/min respectively.